Determinants of Risk Management in the UK Insurance Industry: An Empirical Study - Xiong, Jian (2007)
Abstract: This study focuses on the rationales for risk management in the UK insurance industry, from which the top 29 companies were selected and various measurements of their risk management as measured by their risk management information in their annual reports and performance were measured. Using Logistic and OLS regression analyses the results suggest that there is no correlation between risk management scores and stock performance. However there was a clear negative correlation between risk management score and credit rating, which was used as a proxy for possibility of financial distress. Therefore there is no clear evidence that risk management is used as a signal to shareholders, but there is strong evidence that it is used as a means of avoiding financial distress